Intentional Ecology: Integrating environmental expertise through a focus on values, care and advocacy - Alexandra R. Knight (Springer Nature, 2021)
Abstract As the significance of environmental degradation for humanity becomes apparent, the challenge of developing expertise in integrating science, advocacy and implementation has been acknowledged. Addressing recent and ongoing global challenges including mass extinction, climate change, disease and threats to food, water and power security requires employment of evidence-based science in multi-faceted approaches. Ensuring the mobilisation of new knowledge in practice, both in policy and on-ground actions, takes many researchers into the realm of advocacy, where facts and values become equally important. In the nexus between research and practice, guidance in integrating approaches is required. Drawing on the fields of conservation biology, systems theory and feminist science, this paper offers a new conceptual framework to guide researchers and professionals; one that supports practice by encouraging action and advocacy. The framework, intentional ecology, requires examination of ethics and acknowledgement of the human endeavour that supports curiosity and care in research. Intention is the key concept here as it incorporates beliefs, choice and actions. A case study of the application of intentional ecology to research into, and conservation of, a small, threatened amphibian, Sloane’s Froglet, in South Eastern Australia is provided. Many environmental issues are complex and it is difficult to find a single point to address. While acknowledging that complexity, intentional ecology provides an ethical basis and imperative to act. In so doing intentional ecology enables early, applied and relevant integrated action and reflexive and dynamic approaches to implementation.